Kritik Sastra Kontemporer dan Landasan Ideologis Pemikiran Kritis Adonis terhadap Puisi - Resty Syahrotul Aini; Tatik Mariyatut Tasnimah (Majalah Ilmiah Tabuah: Ta`limat, Budaya, Agama dan Humaniora, 2024)
Arabic literary criticism in its development from the jahiliyyah to the contemporary period continues to undergo changes. The West became one of the causes of reform in the realm of contemporary Arabic criticism which brought modernism in Arabic poetic methods. This research examines the problems that occur in the development of contemporary Arabic literary criticism as well as the ideological and Adonis foundations related to contemporary Arabic literary criticism. The method used in this research is descriptive qualitative with a research design in the form of library research. The results of this study show that contemporary Arabic literary criticism undergoes changes in the search for criticism methods according to the trends that exist in contemporary times. Arab critics adopt Western methodological trends but do not abandon the methods that have existed in Arabia so far. Although through a long process, Arab criticism can adjust the modernist changes. Regarding modernity, there is one literary critic named Adonis who criticises the Arab-Islamic tradition. Adonis' ideology of thought was formed during his intellectual journey. Adonis was influenced in his thinking by Anton Sa'adah and Nitzcshe.